HUBUNGAN ANTARA KONTROL DIRI SISWA DENGAN KECENDERUNGAN BERPERILAKU BULLYING - Jane Akollo (TANGKOLEH PUTAI, 2022)
High self-control is considered good for controlling behavior in order to avoid hurtful behavior, namely bullying. The research objective was to determine the relationship between self-control and the tendency to bully behavior. The research subjects were 129 class XI students. The research sample was determined by cluster sampling method and the data analysis technique used was product moment correlation analysis. The results of the product moment correlation test show that the value of r = -0.308 and p = 0.002 (p = <0.05) means that the self-control variable has a negative and significant relationship to the tendency to bully students. The value of r = -0.308, when squared (r2) becomes 0.095. The coefficient of determination (r2) of 0.095 means that self-control contributes effectively to the tendency of bullying behavior by 9.5% while the remaining 90.5% is influenced by other variables.